Identification of a contact region for peptide on the TAP1 chain of the transporter associated with antigen processing - Nijenhuis, Marga; Schmitt, Sabine; Armandola, Elena A.; Obst, Reinhard; Brunner, Josef; Hämmerling, Günter J. (The journal of immunology, 1996)
The transporter associated with Ag processing (TAP) translocates cytosolic peptides into the endoplasmic reticulum for presentation by MHC class 1 molecules. Recently, the actual peptide translocation step has been suggested to be preceded by binding of the peptide to TAP. In this study, we investigated the peptide binding site of TAP and its relevance for peptide selection by cross-linking of translocatable peptides. Our data demonstrate, first, that for a TAP heterodimer containing the rat TAPu allelic product, which selects peptides on basis of their C terminus, the translocation efficiency correlates with the peptide binding efficiency. Second, peptides having the cross-linker at different positions all label both the TAP1 and the TAP2 subunit after binding to the heterodimer, indicating that both TAP subunits contribute directly to the peptide binding site and contact most or all amino acids of a bound peptide. Third, by enzymatic digestion and the use specific antisera, we identified a domain of human TAP1 that contributes to the peptide binding site. This domain contains the two hydrophobic and thus putative transmembrane regions closest to the ATP binding sites. We conclude that the peptide binding site controls the selectivity of TAP and is composed of domains of both TAP1 and TAP2, which each contact the bound peptide over all or most of its length. Moreover, the major contact site(s) for peptide on TAP1 are located within or close to the two putative transmembrane regions adjacent to the ATP binding site.